1994
DOI: 10.1213/00000539-199408000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of Bupivacaine Cardiotoxicity

Abstract: In nine pentobarbital anesthetized dogs, the global effects of bupivacaine on the heart were examined during and after the onset of bupivacaine cardiotoxicity. The onset of bupivacaine cardiotoxicity was followed by the use of echocardiography to determine the sequence of events. The overall sequence of changes in the heart, demonstrated by the echocardiographic images, was markedly impaired systolic function and right ventricular dilation. The right ventricular dilation was so profound that it was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The correlation between direct depression of myocardial contractility and cardiac arrest induced by bupivacaine is not clear. Coyle et al (15) reported that intravenous injection of bupivacaine significantly decreased systolic function before the appearance of any serious arrhythmia. Our data show that at low concentrations (0.5–4 µM), the inhibitory effect on ventricular contractility was more evident with the racemic and R(+) bupivacaine than with S(–) bupivacaine and 75S:25R bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between direct depression of myocardial contractility and cardiac arrest induced by bupivacaine is not clear. Coyle et al (15) reported that intravenous injection of bupivacaine significantly decreased systolic function before the appearance of any serious arrhythmia. Our data show that at low concentrations (0.5–4 µM), the inhibitory effect on ventricular contractility was more evident with the racemic and R(+) bupivacaine than with S(–) bupivacaine and 75S:25R bupivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiotoxic effects of bupivacaine may arise either by a direct action on the heart or through a reflex mechanism involving the nervous system [16, 19–21]. The present study was designed to measure haemodynamic variables in the presence of mild CNS toxicity at the end of the infusion, and hence the findings would not distinguish between direct and indirect cardiovascular drug effects.…”
Section: Discussionmentioning
confidence: 99%
“…In electrocardiographic and echocardiographic studies performed in the dog, bupivacaine caused a sudden impaired ventricular systolic function followed by profound right ventricular dilation following IV administration, with multiple ECG changes including widening of the QRS complex, bradycardia, ventricular arrhythmias, and electromechanical dissociation. 74 These changes are likely due to the effect on sodium and calcium channels, decreasing myocardial contractility. 75,76 These properties become exacerbated in the anesthetized animal, making the arrhythmogenic potential of bupivacaine even greater at high doses, or with high plasma concentrations seen following inadvertent intravenous administration.…”
Section: Duration Of Anesthesia Of Lidocaine Alone As An Infiltrativementioning
confidence: 99%